The Development of a Palliative Care Massive Open Online Course (MOOC): Process and Perspectives of Instructors - Thojampa, Somsak; Klankhajhon, Sirikanok (International Journal of Psychosocial Rehabilitation, 2020)
Massive Open Online Course (MOOC) is an important higher education for developing countries that learners can access openly through the website. Palliative care course can enhance attitude, knowledge, and self-practice of the learners, including learning-teaching innovation... The objectives were to report the process of developing of MOOC for palliative care and views of instructors who developed the palliative care course. The stage explains the overviews of the design and development phases of MOOC for the palliative care course. The structure and teaching approaches were designed, including types of media based on the objectives, contents, and background of learners. Next, the outcomes from the design phase were used to develop the course over six months. The palliative care course will be tested in the implementation phase over ten weeks. Baseline measures will be collected before starting the palliative care course and preliminary outcomes data after the completion of this course. Thematic analysis of the instructor’s diaries during the design and development phases identified three main themes: (1) Doubts and concern in MOOC (traditional teaching, benefits of MOOC); (2) Challenges to develop MOOC for palliative care (learning and teaching innovation, developing process of MOOC) and; (3) Overcoming barriers (social supports, problem solving approaches). MOOC is new trend in higher education in developing countries. It significantly increases open accessibility of learners and improves the effective teaching and teaching innovation in the 21st Century. The study demonstrated the process of conducting this course and experiences of instructors during the developing of MOOC for palliative care.